Sulfasalazine and temozolomide with radiation therapy for newly diagnosed glioblastoma - Takeuchi, Satoru; Wada, Kojiro; Nagatani, Kimihiro; Otani, Naoki; Osada, Hideo; Nawashiro, Hiroshi (Neurology India, 2014)
A recent phase 1/2 clinical trial argued for caution for the use of sulfasalazine in progressive glioblastoma (GBM). However, the study enrolled patients with recurrent or progressive high-grade glioma indicating that patients recruited probably had severe disease. Thus, the study may not accurately reflect the effectiveness of sulfasalazine for GBM and we hypothesized that earlier sulfasalazine administration may lead to anticancer effects. The aim of this study was to investigate whether sulfasalazine can improve the outcomes of patients with newly diagnosed GBM. A total of 12 patients were treated with temozolomide and sulfasalazine with radiation therapy after surgery. Twelve patients with primary GBM treated with temozolomide and radiation therapy formed the control group. Progression-free survival (PFS), overall survival (OS) and seizure-free survival (SFS) curves were obtained using the Kaplan-Meier method. The survival curves were compared using the log-rank test. The median OS, PFS and SFS did not differ between the groups. Grade 3 or 4 adverse events occurred over the duration of the study in nine (75%) patients. The median SFS was 12 months in nine patients who received sulfasalazine administration for more than 21 days, which was strongly but not significantly longer than the 3 months observed in the control group (P = 0.078). Sulfasalazine treatment with temozolomide plus radiotherapy for newly diagnosed primary GBM is associated with a high rate of discontinuation due to hematologic toxic effects. This treatment may have no effect on OS or PFS, although it may improve seizure control if an adequate dose can be administered.